2014
DOI: 10.4103/0970-0218.132733
|View full text |Cite
|
Sign up to set email alerts
|

Work-related psychosocial hazards among emergency medical responders (EMRS) in Mansoura city

Abstract: Purpose:This research was done to assess levels of psychosocial stress and related hazards [(burnout, depression, and posttraumatic stress disorder (PTSD)] among emergency medical responders (EMRs).Materials and Methods:A comparative cross-sectional study was conducted upon (140) EMRs and a comparative group composed of (140) nonemergency workers. The groups studied were subjected to semistructured questionnaire including demographic data, survey for job stressors, Maslach burn out inventory (MBI), Beck depres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 23 publications
(37 reference statements)
1
33
1
1
Order By: Relevance
“…A study of 260 prehospital providers in Iran demonstrated 47% of EMTs with high levels of emotional exhaustion and 39% with high levels of depersonalization [20]. A similar study in 140 EMTs in Egypt demonstrated 20% with high emotional exhaustion and 9.3% with high depersonalization [21]. Comparing total MBI scores among prehospital providers in LMICs (Romania and Turkey), Indian EMTs appear to demonstrate a higher sense of personal accomplishment, but higher rates of depersonalization and emotional exhaustion.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A study of 260 prehospital providers in Iran demonstrated 47% of EMTs with high levels of emotional exhaustion and 39% with high levels of depersonalization [20]. A similar study in 140 EMTs in Egypt demonstrated 20% with high emotional exhaustion and 9.3% with high depersonalization [21]. Comparing total MBI scores among prehospital providers in LMICs (Romania and Turkey), Indian EMTs appear to demonstrate a higher sense of personal accomplishment, but higher rates of depersonalization and emotional exhaustion.…”
Section: Discussionmentioning
confidence: 95%
“…Only a handful of these include EMTs in LMIC. Studies of EMTs internationally, including varied burnout assessments such as the Copenhagen Burnout Inventory, report work-related burnout rates ranging from 19%-84% [16][17][18][19][20][21]. High intensity work with little control, overwhelming quantity and pace of work, and administrative burdens appear to be key factors contributing to burnout in this "front lines" population [22].…”
Section: Introductionmentioning
confidence: 99%
“…No significant difference in PA was found between the two groups of nurses. A high value of emotional exhaustion is characteristic of people who have lost their motivation and energy for activities [32]. The higher EE rate of nurses working in UHOL standard wards may be due to the higher proportion of women working there.…”
Section: Discussionmentioning
confidence: 99%
“…Resilience in Emergency Medical Responders: A Pilot Study of a Reflective Journal Intervention Using a Mixed Methods Approach to adverse psychological conditions, predominantly to post-traumatic stress disorder (PTSD;Bennet, Williams, Page, Hood, & Woollard, 2004;Kleim & Westphal, 2011;Khashaba, El-Sherif, Ibrahim, & Neatmatallah, 2014). A study by Bennett and colleagues (2004) examining the prevalence of PTSD among 617 British ambulance workers (i.e., paramedics and emergency medical technicians [EMTs]) suggested that two thirds of them were experiencing intrusive and distress-causing memories as a result of job-related content, while an average of 22% (21.8% for paramedics and 22.2% for EMTs; 95% CI 19-26) were meeting the criteria for a PTSD diagnosis (Bennett et al, 2004).…”
Section: Work In Progress Reportmentioning
confidence: 99%